Code-Mixing Types Used by Jody to Ben in Filosofi Kopi and Filosofi Kopi 2: Ben & Jody - Graciela Queen Wijaya; Flora Debora Floris (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study was conducted to analyze code-mixing types used by Jody when talking to Ben in Filosofi Kopi and Filosofi Kopi 2: Ben & Jody. The writers observed code-mixing types used by Jody as director of a coffee shop called Filosofi Kopi, when talking to Ben as barista, who had a lower status than Jody in the coffee shop. In this study, the writers used theory of code-mixing types by Muysken (2000). The writers used a qualitative approach in this study. The findings of this study showed Jody used two types of code-mixing: insertion and congruent lexicalization. He did not use any alternations when talking to Ben.